Preliminary point prevalence of Cognitive Behavioral Therapy for psychosis (CBTp) training in the U.S. and Canada. Issue 4 (2nd October 2022) - Kopelovich, Sarah L.; Nutting, Elizabeth; Blank, Jennifer; Buckland, Helen Teresa; Spigner, Clarence
ABSTRACT: Background: Cognitive Behavioral Therapy for psychosis (CBTp) is recommended by psychosis treatment guidelines in the U.S. and Canada, however accessibilty has not been systematically established and little is known about trainer or training characteristics in these countries. This paper represents the first effort to estimate the population of CBTp practitioners, characterize trainer qualifications and training practices, and calculate a CBTp accessibility estimate. Methods: We oversampled from a known cluster of the target population and supplemented with chain-referral sampling. Respondents completed an online survey pertaining to workforce training conducted since 2005. An accessibility estimate was calculated using published disease prevalence data and national workforce census data. Results: Twenty-five CBTp trainers completed the questionnaire. Respondents were predominantly white female psychologists in hospital or academic settings. Their estimates of practitioners trained in the past 15 years yielded a point prevalence of 0.57% of the combined mental health workforce, corresponding to 11.5–22.8 CBTp-trained providers for every 10, 000 people diagnosed with a psychotic disorder. Survey results showed several differences in training approaches, settings, and funders. Discussion: This preliminary study suggests that CBTp remains inaccessible across these two countries. Future studies should refine the sampling methods to provide a more robust prevalence estimate within each country.